Factors affecting early and long term adaption among post primary intracerebral haemorrhage patients / Sabarisah Hashim - Sabarisah, Hashim (2016)
Stroke due to intracerebral haemorrhage is defined as the rapidly developing clinical signs of neurologic dysfunction related to the focal collection of blood within the brain parenchyma which is not attributed to trauma. A person with stroke related to primary intracerebral haemorrhage (PICH) may exhibit physical disabilities, cognitive deficits, speech problems, emotional difficulties, daily living problems and post stroke complications. Adaptation to achieve greater independence to function in activities is crucial in relation to achieved positive stroke recovery outcomes. This study aimed to determine the early functional adaptation, later (3 months) functional adaptation, improvement over time, and factors associated with achieving the functional recovery of PICH patients admitted at Hospital Universiti Sains Malaysia and Hospital Sultanah Nur Zahirah, Kuala Terengganu, Malaysia. The specific questionnaire includes the Functional Independence Measure (FIM score), National Institutes of Health Stroke Scale (NIHSS), Complication Inventory Checklist (CIC), Patient Health Questionnaire Nine-item Depression Scale (PHQ-9-DS), and Stroke Knowledge Checklist (SKC). A total of 113 subjects were included in the analysis. The subjects consisted of 66 (58%) men and 47 (41.6%) women. Their mean (SD) age were 55.0 (SD=11.8) years. The majority of participants were hypertensive (95.6%). Basal ganglia were the most common area (49.5 %) of bleeding, followed by bleeding in the lobar areas (20.3%) and thalamic (14.1%) of the brain. Fifteen patients (13%) underwent surgery combined with conservative treatment, whereas 98 patients (86%) received conservative treatment. The mean (SD) length of hospitalisation was 12.0 (SD =14.1) days. The total mean (SD) of early functional adaptation score (FIM) was 48.1(30.1), which indicated low functional adaptation in acute recovery phase. Later (3 months) functional adaptation total mean (SD) score was expected at a significantly higher than the early adaptation score, the total mean difference, t (112) = -16.45, p < .05, 95% Cl [-50.6, - 39.7]. This finding indicates that functional adaptation markedly improved at three month post PICH after received treatment and rehabilitation intervention. Multiple linear regression analysis demonstrated that five associated variables statistically predicted as factors affecting of the early functional adaptation score, R2 = .52, F = 22.7, p < .05). Females (β = 9.6, p = .023), intracerebral bleeding in the nonlobar area (β = -16.7, p < .001), higher neurological deficit score (β = - 1.91, p < .001), respiratory infection (β = -16.7, p < .001), and lower stroke knowledge score (β = 2.89, p = .09) were associated with lower early functional adaptation score. The regression analysis of later (3 months) functional adaptation accounted for, R2 = .65, F = 33, p < .05) of the factors affecting later (3 months) adaptation score. Six predictors including young age (β = - 0.82, p < .001), early functional adaptation score (β = .40, p < .001), high stroke knowledge (β = 2.78, p < .001), lack of exposure to urinary infection at three months post PICH (β = -29.1, p < .001), absence of depression at three months post PICH (β = - 0.98, p < .001), and appropriate ICH treatment (β = 22.5, p < .001) were identified as factors associated with the increase in later (3 months) adaptation outcome score at three months post PICH. A better understanding of the factors that affect the adaptation process is essential in the planning of specific stroke education and rehabilitation interventions with the aim of enhancing functional recovery process. Keywords: intracerebral haemorrhage, stroke, stroke related disability, adaptation, post stroke complications.